A comparison of intertidal metazoan biodiversity among different salinity zones of Louisiana coastal marshes - Husseneder, Claudia; Rayle, Patrick; Aker, Benjamin G.; Thomas, W. Kelley; Foil, Lane D. (Frontiers in Environmental Science, 2022)
Tidal marshes are among the most valuable, productive, and vulnerable ecosystems with high biodiversity. Louisiana’s saltmarshes are endangered by natural and man-made stressors, including oil pollution, saltwater intrusion, and land loss due to sea level rise and erosion. Freshwater diversions have been planned to restore sediment input from the Mississippi River to rebuild marsh habitats in South Louisiana. These proposed diversions will undoubtedly change salinity levels, which is a major controlling factor in the distribution of marsh organisms, including those in soil; however, detailed pre-event inventories are lacking. This study describes the diversity of metazoan meiofauna (organisms between 45-500 µm) and environmental DNA in marsh soil collected in 2018 from Barataria and Caillou Bay, Louisiana, across three salinity zones and four distances from the marsh edge. Diversity analyses using 18S rRNA gene metabarcodes identified salinity as a factor impacting soil metazoan composition. Nematoda and Mollusca were equally distributed across salinity zones. Gastrotricha, Bryozoa, Rotifera, and Platyhelminthes were more prevalent in low salinity while Kinorhyncha were not detected in low salinity. Annelida and insects were equally common in low and high salinity but less in mid salinity. Five nematodes (Eumonhystera filiformis, two Prismatolaimus spp., Anoplostoma sp. and Prodorylaimus sp.), two annelids (Marionina southerni and Dendronereis aestuarina), two platyhelminths (Rhynchoscolex simplex and Olisthanella truncula), the gastrotrich Chaetonotus novenarius and four collembola and ostracods appear to be low salinity bioindicators and are expected to expand range with freshwater diversions. No frequently detected organisms were unique to mid or high salinity zones, but four Nematoda (Meleidogyne spartinae, Prochaetosoma sp., Halalaimus sp., and Dichromadora sp.), two Annelida (Alitta succinea and Namalycastis jaya), two Platyhelminthes (Macrostomum kepneri and Mesorhynchus terminostylis), and one Kinorhyncha (Echinoderes sp.) were never detected in low salinity zones. None of the frequently detected taxa were unique for a particular distance from the marsh edge or bay. This dataset will be useful as baseline for assessing how soil communities will change in response to salinity changes caused by freshwater diversions and saltwater intrusion as well as measuring the environmental impact of pollution and other stressors.